1980
DOI: 10.1203/00006450-198002000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and Maternal Hormonal Response to Starvation in the Ewe

Abstract: SummaryFive ewes 90-130 days of gestation with chronically indwelling fetal catheters were studied. Blood samples were drawn each morning simultaneously from the maternal femoral artery, fetal femoral artery, and fetal umbilical vein. Total starvation was begun after blood samples had been drawn on the 3rd morning, but water was given ad libitum. The mean maternal arterial plasma glucose concentration before starvation (73.4 2 31.0 (SEM) mg/100 ml plasma HzO) fell to 54.8 f 5.2 mg/100 ml (P < 0.01) after 24 hr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 17 publications
5
14
0
Order By: Relevance
“…In agreement with earlier reports in sows [1,47] and ewes [51], fructose was not detected in significant amounts (< 0.1 mmol . L -1 ) in maternal blood at any sampling times.…”
Section: Resultssupporting
confidence: 81%
“…In agreement with earlier reports in sows [1,47] and ewes [51], fructose was not detected in significant amounts (< 0.1 mmol . L -1 ) in maternal blood at any sampling times.…”
Section: Resultssupporting
confidence: 81%
“…Ep stein et al [12] found no increase in fetal glu cagon in the rhesus monkey made glucose intolerant with streptozotocin. Similar obser vations have been made in the fetal lamb, in which the concentration failed to change in response to fetal glucose infusion [15], In studies of chronic maternal fasting in the ewe, we found no significant change in the concentration of glucagon in fetal plasma during short-term fasting [37], but did find a trend towards an increased glucagon concen tration with a prolonged fast (more than 6 days) [36]. The purpose of this study was to investigate the effect of exogenous glucagon on fetal glucose, fructose and insulin in the sheep.…”
Section: Introductionsupporting
confidence: 55%
“…In 7 animals fetal samples only were obtained. Following a maternal fast of a minimum of 5 days, control values indicated that concentrations of glucose, fructose and insulin in fetal plasma were lower and of glucagon higher compared to the values when the ewe was fed, as has been pre viously reported [3,31,[35][36][37], Glucagon infusion into the fetus was then again per formed and the effects on the concentrations of glucose, fructose, insulin and glucagon in fetal plasma were similar to those found in the fed state. The fetal glucagon concentra tion ( fig.…”
Section: Fed Ewesmentioning
confidence: 63%
“…Another difference between this model and the models in which hepatic glycogen decreases is that fetal glucagon is not elevated in the hypoglycemic group (34). In a different lategestation fetal sheep model of nutrient deprivation, fetuses subjected to a five-day maternal fast had significantly lower fetal weight and maternal hepatic glycogen content but did not have different fetal glucagon concentrations or hepatic glycogen contents (29,59). In addition, piglets did not have lower liver glycogen contents following a maternal fast for the final 7 or 21 days of gestation (15), and unilateral ligation of the uterine artery in guinea pigs produced IUGR fetuses that had increased hepatic glycogen content (31).…”
Section: Discussionmentioning
confidence: 99%